(untitled) (Sociología y tecnociencia, 2022)
This special issue of the journal Sociology and Technoscience explores the impact of advances in artificial intelligence on economic, political and social life. Artificial intelligence, autonomous learning systems, robotisation, is putting great strain on prevailing patterns of social organisation. It is therefore crucial to examine the possible consequences of the implementation of all current technological possibilities. This reflection can contribute to setting the direction of the innovation process, before the technological determinism that is spreading imperceptibly in many circles. This exercise, moreover, is not only of academic relevance, but becomes crucial for an appropriate anticipation of the challenges of the future